Forest restoration as a double‐edged sword: the conflict between biodiversity conservation and pest control. Issue 6 (21st April 2017) - Kärvemo, Simon; Björkman, Christer; Johansson, Therese; Weslien, Jan; Hjältén, Joakim
Summary: Forestry has markedly changed a large proportion of the world's boreal forests, often with negative effects on biodiversity. As a result, forest restoration is increasingly implemented to counteract the negative effects. However, restoration measures aimed at mimicking natural disturbance regimes could simultaneously increase the risk of unwanted negative effects, such as damage by forest pest species. This study compares the effect of two restoration methods (prescribed burning and gap‐cutting), on both biodiversity conservation and pest control, to provide a basis for solutions to this potential conflict. Bark beetles are ideal for studying this conflict, as this group is both species‐rich and contains notorious pest species. We conducted a unique, large‐scale field experiment in which we compared the effect of two different restoration methods on the abundance, species richness and assemblage composition of bark beetles. In addition, we estimated uncontrolled tree mortality by the number of trees that died post‐restoration. Beetles were divided in two groups, primary and secondary, the former with an ability to kill growing trees. Bark beetle diversity did not differ between treatment groups prior to restoration. However, after restoration, assemblage composition and primary bark beetle abundance differed between the treatments. Furthermore, species richness was higher in burned and gap‐cut stands compared to reference stands. The number of trees that died post‐restoration was highest on burned sites, whereas no difference was found between gap‐cut and reference stands. The number of dead trees was correlated with the number of primary beetles. Synthesis and applications . We demonstrate the potential for a conflict between forest restoration for biodiversity conservation and the potential risk for tree mortality caused by forest pests. This is likely to become a problem in many boreal forests; however, our results suggest that this conflict can be moderated by the choice of restoration method. The restoration method gap‐cutting had a similar positive impact on bark beetle species richness as compared to the burning method, but did not as burning, increase tree mortality. Thus, in areas where there is an apparent risk for pest outbreaks, our data suggest that gap‐cutting should be the chosen method to avoid an unwanted increase in tree mortality at the stand level. Abstract : We demonstrate the potential for a conflict between forest restoration for biodiversity conservation and the potential risk for tree mortality caused by forest pests. This is likely to become a problem in many boreal forests; however, our results suggest that this conflict can be moderated by the choice of restoration method. The restoration method gap‐cutting had a similar positive impact on bark beetle species richness as compared to the burning method, but did not as burning, increase tree mortality. Thus, in areas where there is an apparent risk for pest outbreaks, our data suggest that gap‐cutting should be the chosen method to avoid an unwanted increase in tree mortality at the stand level.